2019
DOI: 10.1186/s12942-019-0169-9
|View full text |Cite
|
Sign up to set email alerts
|

Urban environment as an independent predictor of insulin resistance in a South Asian population

Abstract: BackgroundDeveloping countries, such as India, are experiencing rapid urbanization, which may have a major impact on the environment: including worsening air and water quality, noise and the problems of waste disposal. We used health data from an ongoing cohort study based in southern India to examine the relationship between the urban environment and homeostasis model assessment of insulin resistance (HOMA-IR).MethodsWe utilized three metrics of urbanization: distance from urban center; population density in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Moreover, individuals that have experienced a double burden of malnutrition or undernutrition in early life followed by later overweight/obesity, also pose a substantially enhanced risk of non-communicable diseases (NCDs) [46]. The observed differences in insulin resistance and adipokine levels at baseline between urban and rural groups aligned with the findings from previous studies, showing a higher HOMA-IR and lower adiponectin levels in urban compared to rural population [47,48]. Moreover, after adjustment for BMI, the differences in HOMA-IR, leptin, and adiponectin were no longer statistically significant, indicating a major contribution by BMI.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, individuals that have experienced a double burden of malnutrition or undernutrition in early life followed by later overweight/obesity, also pose a substantially enhanced risk of non-communicable diseases (NCDs) [46]. The observed differences in insulin resistance and adipokine levels at baseline between urban and rural groups aligned with the findings from previous studies, showing a higher HOMA-IR and lower adiponectin levels in urban compared to rural population [47,48]. Moreover, after adjustment for BMI, the differences in HOMA-IR, leptin, and adiponectin were no longer statistically significant, indicating a major contribution by BMI.…”
Section: Discussionsupporting
confidence: 80%
“…Several studies have shown the association between insulin resistance and chemicals such as phthalates and bisphenol A (BPA), which are some of the environmental pollutants present in urban areas. [22,23] Experimental studies on animals have shown that insulin sensitivity is also influenced by nitrogen dioxide (NO2) and PM 2.5 in air pollutants often found in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with previous studies where the urban environment was an independent predictor of insulin resistance. (33) Furthermore, there is evidence that insulin resistance is associated with lipid alterations in early life and overweight/obesity. (34) Thus, our results might also be explained by the high prevalence of obesity and alterations in lipid metabolism among our sample.…”
Section: Discussionmentioning
confidence: 99%